FORMATION OF THE COMPETENCE OF A PRESCHOOL CHILD IN THE PROCESS OF PREPARATION FOR SCHOOL EDUCATION (Academia Science Repository, 2023)
The concept of pre-school education (education of children of senior preschool age) in the comprehensive program "Kindergarten" is based on the main provisions of the Educational System "School". It is aimed at the development and improvement of the content of education for children of senior preschool age and also at the implementation in the educational process of the methodological principles set forth in the "On Education".